Orthogonal spin labeling using click chemistry for in vitro and in vivo applications - Kucher, Svetlana; Lemke, Edward A. (Journal of magnetic resonance, 2017)
Site-directed spin labeling for EPR- and NMR spectroscopy has mainly been achieved exploiting the specific reactivity of cysteines. For proteins with native cysteines or for in vivo applications, an alternative coupling strategy is required. In these cases click chemistry offers major benefits by providing a fast and highly selective, biocompatible reaction between azide and alkyne groups. Here, we establish click chemistry as a tool to target unnatural amino acids in vitro and in vivo using azide- and alkyne-functionalized spin labels. The approach is compatible with a variety of labels including reduction-sensitive nitroxides. Comparing spin labeling efficiencies from the copper-free with the strongly reducing copper(I)-catalyzed azide-alkyne click reaction, we find that the faster kinetics for the catalyzed reaction outrun reduction of the labile nitroxide spin labels and allow quantitative labeling yields within short reaction times. Inter-spin distance measurements demonstrate that the novel side chain is suitable for paramagnetic NMR- or EPR-based conformational studies of macromolecular complexes.
Published online: 2 December 2016
Gesehen am 26.09.2018